Comparison of various clustering algorithms efficiency - Ruzgas, Tomas (Lietuvos matematikos rinkinys, 2002)
This article illustrates the problem of clustering efficiency of Gaussian mixture models using various clustering methods. The results of investigation by simulation are discussed.